Imaging Inflammation in Asthma: Real Time, Differential Tracking of Human Neutrophil and Eosinophil Migration in Allergen Challenged, Atopic Asthmatics in Vivo - Joanna J. Lukawska; Lefteris Livieratos; Barbara M. Sawyer; Tak Lee; Michael O'Doherty; Philip J. Blower; Martin Kofi; James R. Ballinger; Christopher J. Corrigan; Gopinath Gnanasegaran; Ehsan Sharif-Paghaleh; Gregory E.D. Mullen (EBioMedicine, 2014)
Background: It is important to study differential inflammatory cellular migration, particularly of eosinophils and neutrophils, in asthma and how this is influenced by environmental stimuli such as allergen exposure and the effects of anti asthma therapy. Methods: We isolated blood neutrophils and eosinophils from 12 atopic asthmatic human volunteers (Group 1 — four Early Allergic Responders unchallenged (EAR); Group 2 — four Early and Late Allergic Responders (LAR) challenged; Group 3 — four EAR and LAR challenged and treated with systemic corticosteroids) using cGMP CD16 CliniMACS. Cells were isolated prior to allergen challenge where applicable, labelled with 99mTc-HMPAO and then re-infused intravenously. The kinetics of cellular influx/efflux into the lungs and other organs were imaged via scintigraphy over 4 h, starting at 5 to 6 h following allergen challenge where applicable. Results: Neutrophils and eosinophils were isolated to a mean (SD) purity of 98.36% (1.09) and 96.31% (3.0), respectively. Asthmatic neutrophils were activated at baseline, mean (SD) CD11bHigh cells 46 (10.50) %. Isolation and radiolabelling significantly increased their activation to >98%. Eosinophils were not activated at baseline, CD69+ cells 1.9 (0.6) %, increasing to 38 (3.46) % following isolation and labelling. Analysis of the kinetics of net eosinophil and neutrophil lung influx/efflux conformed to a net exponential clearance with respective mean half times of clearance 6.98 (2.18) and 14.01 (2.63) minutes for Group 1, 6.03 (0.72) and 16.04 (2.0) minutes for Group 2 and 5.63 (1.20) and 14.56 (3.36) minutes for Group 3. These did not significantly differ between the three asthma groups (p > 0.05). Conclusions: Isolation and radiolabelling significantly increased activation of eosinophils (CD69) and completely activated neutrophils (CD11bHigh) in all asthma groups. Net lung neutrophil efflux was significantly slower than that of eosinophils in all asthma study groups. There was a trend for pre-treatment with systemic corticosteroids to reduce lung retention of eosinophils following allergen challenge.